Biosensor based on two-dimensional photonic lattice - Irawan, Rudi (2009)
A nanotechnology technique for biophotonics applications is proposed and simulated. The comparison of transmittance spectra of the two-dimensional photonics lattices with different dielectric constant of the circular rods or holes, which show slab structures of two-dimensional photonic lattices composed of a triangular or square array of circular rods or holes, are obviously feasible to be applied for biosensing in lab-on-chip applications.